John Foxe, Samuel Potter and the Illustration of the Book of Martyrs. Issue 1 (1st April 2014) - Evenden, Elizabeth
Abstract: This article explores the production of an edition of John Foxe's Acts and Monuments (more popularly known as the 'Book of Martyrs'), printed by Adam & Co. in 1873. The edition was prefaced by an Irish cleric, Rev. S.G. Potter, who, at the time of production, was vicar of St Luke's parish in Sheffield. This article investigates Potter's career as a Protestant cleric and Orangeman, examining why he might have been chosen to preface a new edition of Foxe's martyrology. Consideration is then given to the illustrations contained within the 1873 edition and what relation they bare to the woodcut illustrations in the editions of the Acts and Monuments printed during Foxe's lifetime. This reveals a markedly different agenda behind the choice of illustration in the Elizabethan and Victorian editions.